Survey on Web Compositioon Based on Semantics - Narayanan, G; Periasamy, Pon (International Journal of Computer Sciences and Engineering, 2025)
The current service composition techniques and tools are mainly designed for use by Service-Oriented Architecture (SOA) professionals to solve business problems. Little attention has been paid to allowing end-users without sufficient service composition skills to compose services and integrate SOA In this paper provides a brief survey of the approaches to semantic integration developed by researchers in the ontology community. The system focus on the approaches that differentiate the ontology research from other related areas. The goal of the paper is to provide a reader who may not be very familiar with ontology research with introduction to major themes in this research and with pointers to different research projects. We discuss techniques for finding correspondences between ontologies, declarative ways of representing these correspondences, and use of these correspondences in various semantic-integration tasks